Discovery of four new Chinese species of Jacobsonina Hebard, 1929 and Blattella Caudell, 1903 (Blaberoidea: Blattellidae) - Yao, Wen-Wen; Li, Qian-Qian; Li, Lin-Wei; Wang, Zong-Qing; Che, Yan-Li (Zootaxa, 2024)
In this study, specimens of Blattellidae collected in China in recent years are analyzed by combining molecular data and morphological characters, and four new species of Jacobsonina and Blattella are described, Jacobsonina plicata Yao & Che, sp. nov., Jacobsonina subapiculata Yao & Che, sp. nov., Jacobsonina ericonvexa Yao & Che, sp. nov., and Blattella punctoria Yao & Che, sp. nov. Photographs of all new species and the key to Chinese Jacobsonina are also included.